Cerebrospinal fluid analysis in chronic recumbent cows with different duration of recumbency - Karthikeyan Balasubramanian; Saravanan, Mani; Veeraselvam Muthusamy; Balakrishnan Singaram; Yogeshpriya Somu; Karthika Koperumselvan; Sasikala Venkatachalam (The Indian Journal of Animal Sciences, 2026)
Chronic recumbency results progressive ischemic muscle damage, systemic inflammation and disruption of the blood brain barrier, leading to neuroinflammation and irreversible recumbency in dairy cows. Aim of the study was to evaluation CSFchangesin chronic recumbent cows with different duration of recumbency.The study was conducted at the Department of Veterinary Medicine and VCC, VCRI, Orathanadu, from January to November 2025. Eighteen recumbent cows unresponsive to routine therapy for more than 24 hours were grouped as 2-5 days, 6-10 days and more than 10 days of recumbency. CSF samples were analyzed for biochemical, electrolyte, lactate, bicarbonate and neurobiomarkers. CSF analysis revealed significant reductions in glucose and increased protein, CK, LDH and neuron-specific enolase, which evident in prolonged recumbency.A significant change in CSF indicates the presence of blood brain barrier disruption and neuroinflammation in more than 10 days of recumbent cows.